2015
DOI: 10.1002/jeab.138
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of the behavior maintained by delayed reinforcers

Abstract: Random-interval reinforcement was arranged for a sequence of pigeon first-key pecks followed by second-key pecks. First-key pecks, separated from reinforcers by delays that included number of second-key pecks and time, decreased in rate as delays increased. Delay functions, or gradients, were obtained in one experiment with reinforced sequences consisting of M first-key pecks followed by N second-key pecks (M + N = 16), in a second where required first-key pecks were held constant (M = 8), and in a third where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…That is, reinforcement of bouts of a particular length seems to differentially strengthen those bouts relative to bouts of other lengths. The hypothesis that reinforcement operates on bouts and not on individual responses is consistent with evidence that bout initiations increase with rate of reinforcement according to Herrnstein's () hyperbola (Shull, ; see also Hill et al, ), with evidence that reinforcement also operates on responses that precede the one that produces reinforcement (Catania, ; Catania, Reilly, Hand, Kehle, Valentine, & Shimoff, ), and, to some extent, with Killeen's (1994) notion of response‐reinforcement coupling. However, one aspect of the present results seems inconsistent with the bout‐length‐as‐response‐class hypothesis: If reinforcement of bouts is expressed in a single population of bout lengths centered near the mean of reinforced bout lengths, why would there be two populations of bout lengths when there is only one ratio requirement (one response in VI 120‐s, five responses in tandem VT 120‐s FR 5)?…”
Section: Discussionsupporting
confidence: 70%
“…That is, reinforcement of bouts of a particular length seems to differentially strengthen those bouts relative to bouts of other lengths. The hypothesis that reinforcement operates on bouts and not on individual responses is consistent with evidence that bout initiations increase with rate of reinforcement according to Herrnstein's () hyperbola (Shull, ; see also Hill et al, ), with evidence that reinforcement also operates on responses that precede the one that produces reinforcement (Catania, ; Catania, Reilly, Hand, Kehle, Valentine, & Shimoff, ), and, to some extent, with Killeen's (1994) notion of response‐reinforcement coupling. However, one aspect of the present results seems inconsistent with the bout‐length‐as‐response‐class hypothesis: If reinforcement of bouts is expressed in a single population of bout lengths centered near the mean of reinforced bout lengths, why would there be two populations of bout lengths when there is only one ratio requirement (one response in VI 120‐s, five responses in tandem VT 120‐s FR 5)?…”
Section: Discussionsupporting
confidence: 70%
“…Several later experiments have shown that variability, normally measured as the dispersion of different sequences, are higher when a variability contingency is in effect, than when it is not (e.g., Denney & Neuringer, 1998;Kong, McEwan, Bizo, & Foster, 2019;Miller & Neuringer, 2000). This finding is highly reliable, and the interpretation of "direct reinforcement of variability" and "variability as an operant dimension" has been widely accepted (e.g., Catania, 2013;Doughty & Galizio, 2015;Dracobly, Dozier, Briggs, & Juanico, 2017;Lee, Sturmey, & Fields, 2007;Locey & Rachlin, 2013;Odum, Ward, Barnes, & Burke, 2006;Rodriguez & Thompson, 2015;Stahlman & Blaisdell, 2011;Stokes, 1995;Stokes, Mechner & Balsam, 1999;Ward, Kynaston, Bailey, & Odum, 2008). Nevertheless, a few researchers (Barba, 2015;Epstein, 2014;Holth, 2012;Machado, 1989Machado, , 1992Machado, , 1993Machado, , 1997Machado & Tonneau, 2012;Marr, 2012) have raised the question of whether direct reinforcement of variability is the most satisfactory view or whether the variability in these experiments is more effectively or pragmatically considered as a derivative of other procedural characteristics.…”
mentioning
confidence: 97%
“…How a reinforcer influences antecedent behavior quantitatively has recently been further documented in an extensive set of experiments by Catania et al (). The thoughtful planning of their approach is comparable to the IRT research by Dews.…”
mentioning
confidence: 92%
“…My definition of IRT is the time period since the previous response ending with a response. By including a terminal response in the definition, one can speak of reinforcing IRTs without it being jargon.3 How a reinforcer influences antecedent behavior quantitatively has recently been further documented in an extensive set of experiments byCatania et al (2015). The thoughtful planning of their approach is comparable to the IRT research by Dews.…”
mentioning
confidence: 99%